2007
DOI: 10.1007/s10404-006-0145-0
|View full text |Cite
|
Sign up to set email alerts
|

Numerical investigation of AC electrokinetic virus trapping inside high ionic strength media

Abstract: A numerical investigation of the mechanism by which viral particles suspended in physiologically relevant (i.e., high ionic strength) media can be electrokinetically sampled on a surface is presented. Specifically, sampling of virus from a droplet is taking place by means of a high frequency non-uniform electric field, generated by energized planar quadrupolar microelectrodes deposited on an oxidized silicon chip. The numerical simulations are based on experimental conditions applied in our previous work with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…As evidenced by the strong fluorescent signal, the 200 nm spheres collect preferentially at the center of the microelectrode array. The driving force for this collection has been shown to be a combination of negative DEP and viscous forces on the spheres exerted by electrothermal fluid flows [ 21 ]. DEP is caused by the direct influence of the spatially non-uniform AC electric field on the polarizable spheres, whereas electrothermal fluid flow stems from the interaction between the electric field and surrounding medium [ 5 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As evidenced by the strong fluorescent signal, the 200 nm spheres collect preferentially at the center of the microelectrode array. The driving force for this collection has been shown to be a combination of negative DEP and viscous forces on the spheres exerted by electrothermal fluid flows [ 21 ]. DEP is caused by the direct influence of the spatially non-uniform AC electric field on the polarizable spheres, whereas electrothermal fluid flow stems from the interaction between the electric field and surrounding medium [ 5 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, it was found that successful M13 phage capture under conditions of negative DEP was not possible. This was attributed to the competing effects between DEP and the strong electrothermal fluid flow that arises in suspending media of high electrical conductivity (here, 880 mS/m) [ 21 ]. For this reason, M13 collection was attempted by means of positive DEP.…”
Section: Resultsmentioning
confidence: 99%
“…Using fluorescent imaging, Docoslis et al (2007) detected captured virus (vesicular stomatitis virus) and later explored numerical simulations of the system to better understand the processes involved (Wood et al, 2007). The virus was captured from physiologically relevant ionic strength media (880 mS m -1 ) at low concentrations (<10 6 PFU mL -1 ).…”
Section: Fluorescence-based Detectionmentioning
confidence: 99%
“…The results suggest reduced hydrodynamic dragging in the AC-biased pore: Whereas the native negative surface charges on the SiN and SiO 2 pore wall induces a cationic flow in direction opposite to the electrophoretic motions of the negatively-charged PS particles under no transverse field 39 , the high-frequency alternating voltage virtually cancel the net counterion motions thereby weakening the electroosmotic flow (EOF) to retard the particle translocation dynamics 40 . It is also noted that in addition to DC-driven hydrodynamics, AC-derived EOF velocity 41 would be diminished rapidly with increasing ω by the fact that the inefficient screening by ions under the high-frequency conditions leads to little potential drop at the electric double layer 37 38 , and hence less counterions to generate the steady water flow.…”
mentioning
confidence: 99%